2019
DOI: 10.24940/theijhss/2019/v7/i4/hs1904-059
|View full text |Cite
|
Sign up to set email alerts
|

Corrective Feedback and its Effects on Memoranda and Letters of Students of Sunyani Technical University, Ghana

Abstract: Corrective Feedback and its Effects on Memoranda and Letters of Students of Sunyani Technical University, Ghana 1. Introduction and Background One of the earliest definitions on CF was given by Chaudron (1977:31) who considered it as "any reaction of the teacher which clearly transforms, disapprovingly refers to, or demands improvement of the learner utterance." Synonyms of CF which have been used by other authors include: error correction, negative evidence, and negative feedback (Méndez et al., 2010:241). Ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…The results of the field data show that DCF is effective in treating errors. The findings are in consonance with Ferris (1999), Chandler (2003), Mubarak (2013), Owusu (2017), Owusu (2019), Owusu (2020.…”
Section: The Influence Of Dcf On Tu Students' Scriptssupporting
confidence: 76%
See 2 more Smart Citations
“…The results of the field data show that DCF is effective in treating errors. The findings are in consonance with Ferris (1999), Chandler (2003), Mubarak (2013), Owusu (2017), Owusu (2019), Owusu (2020.…”
Section: The Influence Of Dcf On Tu Students' Scriptssupporting
confidence: 76%
“…Here, students are left to reread and subsequently edit the errors in their scripts rather than the teacher indicating it clearly. As stated earlier, several empirical studies (for example, Mubarak, 2013;Owusu, 2017;Owusu, 2019;Owusu, 2020) have revealed the efficacy of the DCF method. Consequently, these studies recommended DCF for teachers to use in their various SLA classrooms.…”
Section: Direct and Indirect Cfmentioning
confidence: 87%
See 1 more Smart Citation
“…Because there are always many scripts to be graded by relatively fewer language teachers, the issue of grading of scripts has always been problematic, as teachers use their own style. In Owusu (2019), it was found out that DF and IF have positive effect on students' scripts, and that no feedback (NF) doesn't have a place in grading of texts. This paper is therefore an attempt to find out the effects that DF and IF have on the business communication texts of selected students of Ho Technical University.…”
Section: Layouts (Formats) and Types Of Business Lettersmentioning
confidence: 99%
“…For 5 IF Group members to have maintained the same pre-test results at the post-test stage, as against 2 DF pre-test results which did not change at the post-test level, is a further indication of the superiority of DF over IF. In Owusu (2019), it came to light that both DF and IF have significant effect on learners' written language. The results, therefore, suggest that DF should be embraced in grading the texts of second language learners.…”
Section: 1wcf Type That Has the Greatest Effects On Students' Perfmentioning
confidence: 99%